The Influence of Creativity Level on Overcoming ￼￼￼the Barriers of Teachers’ Professional Development - E. F. Zeer; L. S. Popova (Образование и наука)
The paper summarizes the research findings concerning the influence of creativity on overcoming the barriers of teachers’ professional development. The re- search subject includes defining the interrelations between the creativity and profes- sional burn-out. The aim of the studies is to find out the influencing factors of creativ- ity eliminating the destructive trends of professional pedagogic activity. The methodology is based on the E. E. Simanyuk’s concept describing the de- structive tendencies of teachers’ professional formation and the constructive overcom- ing strategies. The teachers’ refresher course at Sverdlovsk Regional Institute of Education De- velopment was taken as the experimental ground for the research. The diagnostics of the psychological constructs relating to the discussed phenomena was carried out by using tests of high validity and reliability. The modern methods of mathematical statis- tics were applied. The research outputs are of high practical importance both for designing the content of teachers’ professional development and upgrading their readiness for educa- tional innovations.